Rs401681 and rs402710 polymorphisms of CLPTM1L gene in cancerous and healthy lung tissues in patients with lung adenocarcinoma - Joanna Żywiec; Mateusz Rydel; Bogna Drozdzowska; Katarzyna Klimczyk; Janusz Kasperczyk; Damian Czyżewski (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Introduction: The search for factors influencing the survival of patients with lung cancer is still ongoing. It may potentially be a polymorphism of the cleft lip and palate transmembrane 1-like (CLPTM1L) gene, which is involved in the process of carcinogenesis. The aim of the study was to assess the distribution of genotypes and alleles of selected polymorphisms of the CLPTM1L gene - rs401681 and rs402710 - in cancerous and healthy lung tissue in patients with lung adenocarcinoma and their relationship with patient survival. Material and methods: The study included 133 patients with an average age of lung cancer diagnosis of 65 years, who had undergone lung adenocarcinoma surgery in the past. Genetic material - deoxyribonucleic acid (DNA) - was isolated from paraffin-protected specimens of cancerous and healthy lung tissue, and genotyping of CLPTM1L polymorphisms was performed. The obtained results were analyzed along with demographic data, history of smoking, family history of cancer, stage of the disease in the tumor, node, metastasis (TNM) classification, clinical stage of the cancer and the survival time of the patients. Results: The mean follow-up period was 44.5 months. The patients who died lived an average of 22.6 months from the time of cancer diagnosis. There were no significant differences between the distribution of genotypes or alleles in the cancerous and healthy tissues and their relationship with the survival of the patients. The age at the time of diagnosis of cancer, category N in the TNM classification and high clinical advancement of the cancer were the only factors influencing the survival of the patients. Conclusions: No relationships between the polymorphic variability of rs401681 and rs402710 in cancerous and healthy lung tissue and the survival of patients were found.